1) (x^2-5x)(x^2+5x-2)=24 2) (2x^2+x+1) (2x+x+3)=8 3)x^4-10x^2+9=0 4)36x^4-7x^2-4=0

0 голосов
79 просмотров

1) (x^2-5x)(x^2+5x-2)=24
2) (2x^2+x+1) (2x+x+3)=8
3)x^4-10x^2+9=0
4)36x^4-7x^2-4=0


Алгебра (22 баллов) | 79 просмотров
Дан 1 ответ
0 голосов

3. x^4-10x^2+9=0
   (x^2)2 -10x^2 +9=0
   теперь подставляем переменную t
   t^2 -10t^2+9=0
   Находим дискриминант D= (-10)^2 - 4*1*9= 100-36=64  D>0 (два корня)
  t1= 10-8/2=1
  t2= 10+8/2=9
  находим х по формуле : x^2= t
 x^2=t1      x^2=t2
 x^2=1       x^2= 9 
 x= +-1      x= +- 3 

ответ: +- 1 и +- 3

(92 баллов)